The ones above and the ones below: Comparative analysis of urban policies of the districts of El Agustino and San Isidro in Lima, Peru - Espinoza Prado, Gelin (2018)
The public space has recently become the protagonist of urban transformations, especially because it expresses the complexities of globalization. Therefore, urban agglomerates are currently contesting leadership spaces of different natures (financial, cultural, etc.). This situation turns cities and their governments into fertile ground to promote changes and also into scenarios in which all social contradictions are expressed. The present article analyzes the urban policies deployed by two districts of Metropolitan Lima: El Agustino and San Isidro. The districts to be studied were chosen by virtue of their different income levels: while San Isidro is one of the districts of Lima with the highest income, El Agustino is considered as a low-income district. Our analysis model offers criteria to examine in a comparative way the phenomenon of urban governance in two generally different districts. With the evidence, we conclude that despite the significant differences in the type of implemented policies, both districts need to improve the degraded spaces in order to allow the universal accessibility and the redistribution of opportunities among the population. These challenges pose the need to define a new urban agenda where a feminist and universal design approach is present for the implementation of policies that allow the proper functioning of public services. In order to achieve our objective, a qualitative methodology was applied; it required the review of management documents, web pages and, at the same time, observations of the urban space, as well as a set of semi-structured interviews to authorities and former municipal authorities.